Komponen Sebuah Perjalanan Wisata (Tour) - I Wayan Wijayasa (UHN IGB Sugriwa Denpasar, 2017)
Tour consists of six important elements. Those are (1) transportation which can be land, sea, or air transportation. (2) Acommodation that can be an expensive resort or a small and simple motor inn. (3) Dining can be a qick-service food, buffet dinner, or table service dining. (4) Sightseeing; which can be a city tour, rural or village tour to historical sites, traditional architecture, or (5) Attraction is actually the most important pulling factor motivation of the tourists’ visit to a destination which can be a performance, an adventure activities, etc. (6) Shopping which can be a big super-market, traditional art market, or galleries. A tour plan is made in the form of 3 different itineraries. Those are (1) summary itinerary, (2) Detail Passenger Itinerary or DPI, and (3) Escort itinerary which is also welknown as Manual. A tour itinerary must consider all six elements in accordance with the clients’ interests, budget, number, and time alocation for a tour